How Risky People of Getting COVID-19 based on Their Daily Activities? - Ariyanti, Fajar; Mustakim, Mustakim; Al Ayubi, Moch T A; Marlisman, Desty Pratiwi (Kesmas, 2021)
In Indonesia at the end of 2020, COVID-19 cases were increasing and predicted to continue, as it had not yet passed the peak of the pandemic curve. The government had implemented mobility restrictions to reduce exposure to COVID-19. This study aimed to identify the risk of people getting COVID-19 based on their daily activities. Using a cross-sectional design, this study took 315 respondents under non-probability sampling from September to October 2020. Thedata were analyzed using the Chi-square test with α 0.05. This study showed that the risk percentage of people infected with COVID-19 based on their daily activities was 15.56% at low-risk, 63.81% at moderate-low risk, 17.14% at moderate risk, and 3.9% at moderate-high risk. Factors that were significantly related to the risk of getting COVID-19 in terms of daily activities were sex, attitude, and COVID-19 preventive behavior. In brief, the risk of getting COVID-19 could be assessed from daily activities carried out during the pandemic's peak.